Pengaruh Relationship Marketing dan Customer Value terhadap Customer Satisfaction untuk meningkatkan Customer Loyalty - pangerapan, Gladies judith (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
Banking system offering product and services to attract customers. Various type nof innovations and changing are consider to provide highly attraction of customer feel satisfy to the product and services and become loyal to a bank. Not only for funding but also for lending. For regional banks, which is central to regional financial transactions, improvements need to be made so that they can continuing to maintain and increase customer loyalty. The aim of the study to determine the role of relartionship marketing and customer value that provide satisfaction for customer increasing customer loyalty of customer credit of PT. Bank SulutGo Sub branch Tuminting . The analysis used path analysis and taking sampling to existing credit customers at PT. Bank SulutGo Sub Branch TumintingKeywords: Relationship Marketing, Customer Value, Trust, Commitment, Communication, Conflict Handling